2020
DOI: 10.1212/wnl.0000000000010945
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GGC repeat expansion in the NOTCH2NLC gene in amyotrophic lateral sclerosis

Abstract: ObjectiveTo determine whether the GGC repeats in the NOTCH2NLC gene contribute to amyotrophic lateral sclerosis (ALS).MethodsIn this study, 545 ALS patients and 1,305 healthy controls from mainland China were recruited. Several pathogenic mutations in known ALS-causative genes (including C9ORF72 and ATXN2) and polynucleotide repeat expansions in NOP56 and AR genes were excluded. Repeat-primed PCR (RP-PCR) and GC-rich PCR were performed to determine the GGC repeat size in NOTCH2NLC. Systematic and targeted clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 47 publications
0
62
0
Order By: Relevance
“…NIID is a neurodegenerative condition characterized by eosinophilic intranuclear inclusions in neuronal and glial cells, which have characteristic findings on brain MRI, including high diffusion-weighted imaging signals along the corticomedullary junction [ 4 , 95 , 152 ]. The NOTCH2NLC expansion has also been found in a rapidly growing number of phenotypes, including leukoencephalopathy, essential tremor, Parkinson’s disease, multiple system atrophy (MSA) and amyotrophic lateral sclerosis [ 38 , 69 , 95 , 117 , 119 , 175 ]. Further long-read sequencing studies have found noncoding CGG repeat expansions in LOC642361/NUTM2B-AS1 , LRP12 and GIPC1 [ 69 , 172 ].…”
Section: Recent Discoveries For Neurological Repeat Expansion Disordersmentioning
confidence: 99%
“…NIID is a neurodegenerative condition characterized by eosinophilic intranuclear inclusions in neuronal and glial cells, which have characteristic findings on brain MRI, including high diffusion-weighted imaging signals along the corticomedullary junction [ 4 , 95 , 152 ]. The NOTCH2NLC expansion has also been found in a rapidly growing number of phenotypes, including leukoencephalopathy, essential tremor, Parkinson’s disease, multiple system atrophy (MSA) and amyotrophic lateral sclerosis [ 38 , 69 , 95 , 117 , 119 , 175 ]. Further long-read sequencing studies have found noncoding CGG repeat expansions in LOC642361/NUTM2B-AS1 , LRP12 and GIPC1 [ 69 , 172 ].…”
Section: Recent Discoveries For Neurological Repeat Expansion Disordersmentioning
confidence: 99%
“…4, Supplementary Figure 1), which were in the pathogenic range of GGC repeat (>40 repeats). 22 Hence, these results suggested that the GGC repeat expansion in the 5'UTR of NOTCH2NLC is associated with the clinical manifestations observed in these patients.…”
Section: Identification Of Ggc Repeat Expansion In Notch2nlcmentioning
confidence: 74%
“…To date, GGC repeat expansion of NOTCH2NLC has been reported to not only be responsible for typical NIID, [1][2][3][4] but also associated with a group of NOTCH2NLC-related repeat expansion disorders (NRED). 14 These disorders include Alzheimer's disease (AD), 3 frontotemporal dementia, 15 parkinsonism-related disorders, 3,16,17 multiple system atrophy (MSA), 18 essential tremor (ET), 19,20 adult leukoencephalopathy, 21 amyotrophic lateral sclerosis (ALS), 22 and oculopharyngodistal myopathy (OPDM), 23,24 Studies so far showed an indefinite tendency between the length of GGC repeat expansion in the NOTCH2NLC and the variable NRED phenotypes: intermediate-length from 41 to 130 repeats (median 47 repeats) are potentially associated with Parkinson disease, 16,17 length from 44 to 143 repeats (median 75 repeats) are related to ALS, 22 around 100 repeats usually dominantly associated with dementia-type NIID, and long expansions with more than 200 repeats may be associated with muscle-type NIID or OPDM. 14,23,24 This indicates that the spectrum of NRED is highly complicated and may be closely related to the number of expanded GGC repeats, whereby it is worthy to further investigate whether there are new clinical subtypes of NRED and understand the relationship between the GGC repeat numbers and the heterogeneity of NRED.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations